Impact of Risk Management Practices on Bank Performance: A case of Banking Sector in Pakistan - Bushra Zulifqar; Akmal Shahzad; Saima Younas (International Journal of Business and Economic Affairs, 2022)
This paper aims to investigate the impact of risk management practices on the banking sector of Pakistan. Papulation of this study was the employee in the banking sector in the risk management department. The researcher used random sampling to collect data to test the hypothesis of this study. The researcher used SEM to analyze this study. The result reveals that the independent variables, i.e., risk management, level of risk control & monitoring, risk identification, and level of risk control & monitoring, was positive and significant on the dependent variable, i.e., bank performance. The researcher recommended that a comparative analysis of both Islamic and conventional banking be conducted in the future.